Examination of Prosodic and Musical Structures of Muammer Sun’s Original Songs - İvan Celac (Konservatoryum)
Muammer Sun (1932-2021) gave importance to prosody. In prosody, the word that is to be emphasized in the sentence should be given the highest sound in the melody. In rhythmic harmony, the syllables in the word are separated by their length and shortness, and accordingly, short or long note values are given in the melody. The main question is how Sun uses lyrics and music features together in his songs. His vocal musical repertoire has a wide variety. Therefore, only his original songs composed for a single adult soloist were evaluated. Four original songs, identified specifically for this study and whose notations were obtained, were examined in terms of prosodic and musical features. The analysis (meter harmony, high pitch harmony, semantic harmony/phrase emphasis and others) applied to the relevant songs constituted the method of the research. In this study, in addition to the prosody in the four original songs of Muammer Sun, structures such as tonal/modal understanding, measurement (rhythm) and scale, melodic structure/intervals, the relationship between high pitches and syllables/letters, and sound width are analyzed. findings have been reached. From the determined findings, the relationship of Sun’s four songs with the relevant theory is presented as a result.